Contemporary pandemics and ethics in science teaching - Albuquerque, Nathalia Fogaça; da Rocha Filho, João Bernardes (Debates em Educação, 2022)
The text alerts science teachers to the need to introduce ethics, and in particular the ethics of life, in the education. The proposal is based on current environmental and ethical issues that arise from anthropocentrism, offering the pandemics of the 21st century as an example the. The cosmocentric, senciocentric and biocentric positions are exposed and analyzed, in the sense of legitimizing actions in the scope of science education, that contribute to overcoming the anthropocentric perspective. The text suggests that the continuity of this biased culture depends, in part, on the immutability of certain traditional discourses, scientific articles and didactic texts in science education, in which remnants of speciesist ideology underlie. In conclusion, the text recalls that the civilizing process achieved slow, but successive advances throughout history, which allows us to predict that the ethics of life will eventually overcome the reactionary forces linked to tradition and profits, inaugurating an era of greater awareness, with people assuming ethical commitments regarding the maintenance of life and the rights it confers on beings.